Biotransformation of carbamazepine by laccase-mediator system: Kinetics, by-products and toxicity assessment. (April 2018) - Naghdi, Mitra; Taheran, Mehrdad; Brar, Satinder K.; Kermanshahi-pour, Azadeh; Verma, M.; Surampalli, R.Y.
Graphical abstract: Highlights: Temperature and pH affected the removal of carbamazepine with the laccase-ABTS system. Maximum degradation efficiency of carbamazepine with laccase-ABTS was up to 95%. Laccase cannot reach more than 32% degradation efficiency in the absence of ABTS. Abstract: Carbamazepine (CBZ) is one of the most detected pharmaceutical compounds around the world, with adverse human and animal health impacts in wastewater effluents. Recently, biocatalytic degradation using ligninolytic enzymes such as laccase along with redox mediators provides a promising approach for their removal from water and wastewater. However, the effects of operational parameters on biotransformation need to be investigated in order to design a robust and efficient process. In this research, central composite design was performed and analyzed using response surface methodology to study the effects of temperature, pH, enzyme concentration and mediator concentration. The adequacy of the developed model was confirmed by the coefficient of multiple regression (R 2  = 75.97%) indicating a reasonable model for practical implementation. The results showed that performing the biotransformation at 35 °C, pH 6, with 60 U/L of enzyme concentration and 18 μM of mediator concentration resulted in 95% removal of CBZ. 10, 11-Dihydro-10, 11-dihydroxy-CBZ and 10, 11-dihydro-10, 11-epoxy-CBZ were identified as the major metabolites of CBZ oxidation by laccase. The estrogenicity tests indicated that the CBZ with an initial concentration of 4 μM and its biotransformation products had no estrogenic effect. The successful transformation of CBZ demonstrated the potential of the laccase-mediator system for the removal of recalcitrant micro-contaminants.